2013
DOI: 10.1097/acm.0b013e31828acf27
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Population Health

Abstract: A 2012 Institute of Medicine report is the latest in the growing number of calls to incorporate a population health approach in health professionals’ training. Over the last decade, Duke University, particularly its Department of Community and Family Medicine, has been heavily involved with community partners in Durham, North Carolina to improve the local community’s health. Based on these initiatives, a group of interprofessional faculty began tackling the need to fill the curriculum gap to train future healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Some learners reported that the CHAMP curriculum "could" increase recruitment of high-quality candidates, while others felt that this curriculum would not differentiate our program as all family medicine residencies would have a rigorous community health and advocacy education experience. This discrepancy in perception affirms what Kaprielian et al found in developing their population health competency map 16 and suggests that clearly outlining the longitudinal and progressive CHAMP curricular components will increase understanding of CHAMP's scope, foundation, and strategic priority within the residency (in alignment with program pillars of advocacy and caring for underserved populations) and ease communication with learners.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Some learners reported that the CHAMP curriculum "could" increase recruitment of high-quality candidates, while others felt that this curriculum would not differentiate our program as all family medicine residencies would have a rigorous community health and advocacy education experience. This discrepancy in perception affirms what Kaprielian et al found in developing their population health competency map 16 and suggests that clearly outlining the longitudinal and progressive CHAMP curricular components will increase understanding of CHAMP's scope, foundation, and strategic priority within the residency (in alignment with program pillars of advocacy and caring for underserved populations) and ease communication with learners.…”
Section: Discussionsupporting
confidence: 65%
“…CHAMP is a unique longitudinal curriculum for family medicine residents designed to integrate tools and skill building in community health, population health and management, advocacy, and health disparities into clinical practice. Drawing on selected elements from published programs, 13, [16][17][18][19] CHAMP longitudinal curriculum incorporates community partnerships, population analysis, and specialty clinical experiences to teach residents to identify and address SDH and health disparities in our community and clinics. CHAMP emphasizes identification of SDH and their downstream effects on health, and teaches residents to engage community members, leverage population health data, and build and lead interdisciplinary teams to address health disparities consistent with ACGME Family Medicine community and public health milestones.…”
Section: Champ Curriculum Structurementioning
confidence: 99%
“…Current recommendations insist on following a competency-based approach starting with "backward planning" that first specifies local health issues. Once the most pertinent problems are identified, desired competencies and well defined learning outcomes are developed and integrated into the curriculum to address those predetermined community needs (20)(21)(22)(23). The authors therefore recommend that public health academic programmes in Pakistan be restructured to achieve greater alignment with evolving community and health system needs.…”
Section: Area Of Inquiry 2: Knowledge and Skill Sets That The Fresh Gmentioning
confidence: 99%
“…The acquisition and demonstration of competencies based on professional standards are particularly well-suited to human service professions, including education, nursing and social work (Hagenhauer & Volet, 2014). Competency statements have been developed to clearly describe what students should be able to do and professional programs have been designed around these (Kaprielian et al, 2013;Thompson, Harver, & Eure, 2009). Salm, Johner, and Luhanga (2016) assert that developing required competencies related to specific standards help to determine whether students had the technical and professional skills and were professionally competent for their chosen profession.…”
Section: Competency Approachmentioning
confidence: 99%